The dynamic nature of connection and its relation to character in youth sport - Herbison, J. D.; Vierimaa, M.; Côté, J.; Martin, L. J. (International Journal of Sport and Exercise Psychology, 2019)
Positive youth development (PYD) is an asset-oriented approach to adolescent development that has been adapted to sport. Interestingly, in sport, the PYD outcomes (i.e. competence, confidence, connection, and character) have largely been introduced as outcomes, with little attention to their dynamic nature or individual influences over time. In considering evidence from educational settings that indicates peer relationships fluctuate over time, the current project sought to explore the dynamicity of these relationships (i.e. connection) over the course of an athletic season. In addition, the potential for connection towards the beginning of a sport season to influence athlete character towards the end of the season was assessed. Athletes from five elite youth volleyball teams (N = 43 athletes; Mage = 15.86; SD = 1.17) completed peer nomination questionnaires (i.e. connection) at the beginning and end of an athletic season. At the end of the season, a practice session was videotaped and athlete behaviours were coded for frequency of prosocial and antisocial behaviours (i.e. character). Results indicate significant variability in connection over the course of a season, and those who were rated as popular by their team members at the beginning of the season were more likely to demonstrate prosocial behaviours at the end of the season. Discussions pertaining to the novel methodologies implemented, as well as the theoretical and practical implications of the results are advanced herein.